2010
DOI: 10.1353/csd.0.0127
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Doctoral Experience of Asian International Students in the Science, Technology, Engineering, and Mathematics (STEM) Fields: An Exploration of One Institutional Context

Abstract: In this study, we explored the experience of Asian international doctoral students in the Science, Technology, Engineering, and Mathematics (STEM) fields at one research-extensive university. We found that Asian international doctoral students in the STEM fields at this institution were often isolated from their peers and faculty, faced an array of issues including the lack of funding, the choice of advisor, and other departmental issues distinct to their international student status. Implications for policy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 26 publications
3
72
0
Order By: Relevance
“…Historically, policies have focused on the development of knowledge and skills in the area of STEM. However, interest in STEM is declining in high school students for most student populations, with the exception of Asian students (Le, & Gardner, 2010). Appropriately, programs have shifted from a singular focus on STEM achievement to a more holistic approach to STEM talent development.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, policies have focused on the development of knowledge and skills in the area of STEM. However, interest in STEM is declining in high school students for most student populations, with the exception of Asian students (Le, & Gardner, 2010). Appropriately, programs have shifted from a singular focus on STEM achievement to a more holistic approach to STEM talent development.…”
Section: Introductionmentioning
confidence: 99%
“…Some research investigated Asian international graduate students' experiences (e.g. Le & Gardner, 2010;Sato & Hodge, 2009), Chinese international students' personal and sociocultural stressors (e.g. Yan & Berliner, 2013), and international students' cultural adaption (Chirkov, Safdar, de Guzman, & Playford, 2008).…”
Section: Issues Related To Extrinsic Motivationmentioning
confidence: 99%
“…Further, family influence was found in research (e.g. Le & Gardner, 2010;Zhou, 2014). Family influence questions were also included in the instrument.…”
Section: Instrumentmentioning
confidence: 99%
“…International PhD students had different research interests from their advisors which hinder their progress and meeting the requirement at the expected time (Weiner, 1992). Due to the family background or countries of origin some students also were found to be challenged by the financial constraints and need of fulfilling the needs of everyday life (Le and Gardner, 2010;Sato and Hodge, 2009). Identifying the motivational cause and challenging barriers hindering the attainment of the graduation requirement were not much focused and few researches were only conducted in some countries.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…From above views grouped into GR1, GR2 and GR3, it is well observed that all international PhD students are highly motivated by different external factors such expectation of good job (Green, 1992;Pennington, 1995;Porter et al, 2003;and Robbins, 2003); good payments (Deci and Ryan, 1985); fear to spend their time without good results, pressures from family background and community (Le and Gardner, 2010) and finally the expectation of respect and the shame of returning home without their PhD degree certificates (Golde, 2005;Lovitts, 2008).…”
Section: External Motivation To Pursue Phd Studies In Mathematics Andmentioning
confidence: 99%